Introduction to the Forum: Muslim modernity in South Asia - Mir, Farina (Modern Asian Studies, 2024)
This short article introduces the Forum on Muslim modernity in South Asia, placing its four articles-by Muhammad Qasim Zaman, SherAli Tareen, Julia Stephens, and Justin Jones-in the context of existing scholarship. I highlight the authors' contributions to the study of Islamic reform and of women's agency, in particular, in understandings of Muslim modernity in South Asia. Each of the contributions is on a discrete topic; this introduction therefore endeavours to pull at the threads within each that underscores their interventions in the study of Muslim modernity and that tie them together in this Forum.
Keywords: Colonial India; Islam; Islamic Reform; Modernity; Gender